(untitled) (American Journal of Technology and Applied Sciences, 2025)
In this article, for a more accurate assessment of the operation of various dust collectors, when assessing the performance of dust cleaning devices, the area and size of industrial buildings where enterprises are located are taken into account. Dust collectors are designed to clean ventilation (aspiration) waste into the atmosphere if the dust concentration in this waste exceeds the permissible sanitary standards.